In Vitro Antioxidant and Antibacterial Activities of Medicinal Flower Laligurans Rhododendron arboreum Collected from Kathmandu Valley, Nepal - Anil Kumar Jha; Monowar Alam Khalid; Shyam Narayan Labh (International Journal of Food Science)
Rhododendron arboreum, known as Nepal’s national flower and belonging to the Ericaceae family, thrives throughout the Himalayan region. This study investigates the antioxidant and antimicrobial potential of Rhododendron arboreum flowers. Three different extracts were prepared at concentrations ranging from 10 to 640 μg/mL and assessed for their total phenolic content (TPC), total flavonoid content (TFC), and DPPH radical scavenging activity. Results showed significant accumulation of antioxidant compounds (P<0.05), with TPC levels of 37.78, 67.29, and 53.46 mg GAE/g and TFC values of 49.46, 67.46, and 65.71 mg QE/g for LGP, LGE, and LGA at 640 μg/mL, respectively. DPPH activity was highest in LGE (96.33%), followed by LGA (87.11%) and LGP (76.59%), compared to the standard (77.38%). The antibacterial properties were significant against Aeromonas hydrophila, Staphylococcus aureus, and Escherichia coli at 100% concentration, with inhibition rates of 15%, 16%, and 17% for LGP, LGE, and LGA, respectively. These findings indicate that Rhododendron arboreum petals, rich in bioactive compounds, possess strong antioxidant and antibacterial properties, making them potential candidates for developing cost-effective therapeutic formulations. Further research should focus on isolating specific bioactive compounds and understanding their molecular mechanisms to enhance therapeutic efficacy.